Analysis of Implementing K-12 Program on Teachers' Pedagogical Approaches and Their Challenges - Mohammad, Nhelbourne K.; Hongliang, Ma; Sulisworo, Dwi (The Indonesian Institute of Science and Technology Research, 2023)
The Philippines is the only country in Asia, and one of only three countries worldwide, with 10-year pre-university cycle curricula, and its implementation was unstoppable due to global competency demand. However, it has many challenges during the pre-implementation phase due to inadequate school facilities and needing more teachers. Thus, the study aimed to analyse the pedagogical approaches and challenges among teachers in implementing the K-12 curriculum by utilising a descriptive analysis. The design is a fact-finding study with an adequate and precise analysis of the findings. The results of this study, teachers in public schools still need to be fully equipped with pedagogical approaches in teaching K-12 curriculum. Teachers still need to capacitate this new trend in the educational system. The study is plotting to benefit and contribute to those involved in this educational system.